2019
DOI: 10.1002/smtd.201900212
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nickel Film Protected n‐Type Silicon Photoanode with High Photovoltage for Efficient and Stable Oxygen Evolution Reaction

Abstract: n‐type silicon (n‐Si) is a promising photoanode candidate for photoelectrochemical (PEC) water splitting. However, severe chemical corrosion, sluggish reaction kinetics as well as extremely low photovoltage are critical limitations hampering its PEC performance. This paper describes the introduction of a metallic nickel (Ni) thin film as a multifunctional layer that 1) forms a Schottky junction to extract a high photovoltage, 2) provides an electrocatalytic surface for oxygen evolution reaction (OER), and 3) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…The SiO 2 layer is evident from the ≈0.5 nm white layer between the Si and HfO 2 . An adventitious SiO 2 layer has been observed in other ALD studies on HF‐etched Si,31,48,53 and it was similar for all samples so its effect should be uniform among samples.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…The SiO 2 layer is evident from the ≈0.5 nm white layer between the Si and HfO 2 . An adventitious SiO 2 layer has been observed in other ALD studies on HF‐etched Si,31,48,53 and it was similar for all samples so its effect should be uniform among samples.…”
Section: Resultssupporting
confidence: 67%
“…Finally, we note that several MIS water splitting systems have achieved over 600 mV of photovoltage through a combination of using relatively high doped Si and using high‐quality oxides with minimal surface states 30,45,53. As shown by the black region in Figure 6, even an ideal system with optimized insulator thickness may still fall significantly short of the photovoltage limits.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In order to prevent the degeneration of Si photoanodes, numerous studies reported on the use of protection layers consisting of insulating or semiconducting materials. These layers are typically applied onto Si by physical deposition methods such as atomic layer deposition (ALD) . In addition to this protective layer, a catalytic coating, generally deposited by evaporation or sputtering, is commonly used to enhance the OER kinetics …”
Section: Introductionmentioning
confidence: 99%